PERSEPSI KARYAWAN TERHADAP IMPLEMENTASI SISTEM KONTRAK KERJA PADA PT.WAHANA KARSA SWANDIRI DI KECAMATAN MANDAU KABUPATEN BENGKALIS - Ernawaty Tambunan; Syamsul Bahri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
This research was conducted in PT.Wahana Karsa Swandiri Mandau District Bengkalis Regency with the problem that is (1) What are the elements of work contract system that has been agreed by management company with employees at PT.Wahana Karsa Swandiri Sub Mandau Bengkalis Regency? (2) How employee's perception on work contract system at PT. Wahana Karsa Swandiri Mandau District Bengkalis Regency and what factors affect the employee's perception of the implementation of the contract system? The purpose of research to determine the elements of the system of employment contracts and to determine employee perceptions of the implementation of the contract system at PT. Wahana Karsa Swandiri. This research is a quantitative research. Sampling technique used in this research is to use Simple Random Sampling, with 93 respondents. To collect data, researchers used questionnaires, interviews and documentation. Data obtained from the results of this study were analyzed by using quantitative method dekskriptif. The results showed that employee perceptions of the implementation of the contract system on PT.Wahana Karsa Swandiri in Good category. Elements of work contract system such as company regulations, social security, wages, and termination of employment is well executed as well as factors affecting the employee that is internal and external factors form of employee perception in the form of positive. Keywords : perception, work contract system